Sport coaches' experiences of athlete injury: the development and regulation of guilt. Issue 2 (3rd July 2017) - Martinelli, Laura Ann; Day, Melissa Catherine; Lowry, Ruth
Abstract: This study sought to examine coaches' experiences of guilt in the specific context of athlete injury. In-depth, semi-structured interviews were utilised to generate data. Our analysis suggested that not only was guilt a commonly felt emotion, but was also one that that the participants attempted to regulate. The coaches' stories were primarily, although not exclusively, interrogated using the psychological theorising concerning trauma-related guilt. We conclude the paper by making connections to, and from, the coaches' experiences of guilt with existing critiques of the prevailing deontological approach used to define what it means to be a 'good' sport coach. Here, we suggest that dominant perspectives in coach education may be instrumental in entrenching coaches' experience of guilt.